2014
DOI: 10.5901/ajis.2014.v3n6p265
|View full text |Cite
|
Sign up to set email alerts
|

A Human Capital Evaluation of Graduates from the Faculty of Management Sciences Employability Skills in South Africa

Abstract: Previous research on employability has underscored the supply side perspective which for the most part focuses on curriculum design and teaching methods. However, ultimately

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Research on HC has established that higher education is an investment for productivity in the labour market (Fincher 2007;Jonck 2014). This is supported by (Cai 2013, 3) who states that 'education increases individuals' productivity, which consequently enhances job performance'.…”
Section: University and The Economymentioning
confidence: 91%
“…Research on HC has established that higher education is an investment for productivity in the labour market (Fincher 2007;Jonck 2014). This is supported by (Cai 2013, 3) who states that 'education increases individuals' productivity, which consequently enhances job performance'.…”
Section: University and The Economymentioning
confidence: 91%
“…This study could be classified as an ex post facto research design as respondents were related to the different variables prior to data collection. Thus, participants were not assigned to experimental and/or control groups (Jonck, 2014). As a result of this, three limitations of a pretest-post-test research design can be identified, namely the absence of a control group against which comparisons can be made, the teaching effect and the unobserved moderating variables intrinsic to the facilitator (Wagner, Kawulich & Garner, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The theoretical debate on soft skills and employability is related to human capital theory and to human development or capabilities theory (Jonck, 2014). The human capital theory termed education as an essential key in building economy and treated it as an essential aspect to be competent in global economic advancements (Becker, 2009;Bridgstock, 2009;Rothwell & Arnold, 2007;Van Loo & Rocco, 2004).…”
Section: Theories Related To Employability and Soft Skillsmentioning
confidence: 99%